Approved revenue recurrent and capital estimates, 1991 - Federal republic of Nigeria (Lagos : The Federal Government Press, 1991)
This book is the 1991 fiscal year approved current revenue and capital estimates of the federal government of Nigeria.
Title from cover.
rpm 23/01/2019
Ref
Keywords: Revenue; Nigeria